Optimal line planning for multibeam line measurement based on improved algorithms - Meng, Yuanke; Lei, Yusheng; Kang, Yikun; Zhao, Yiyuan (Transactions on Computer Science and Intelligent Systems Research, 2024)
In this paper, this paper address the challenges of multibeam line measurement in the sea by first analyzing the correlation between two-dimensional (2D) and three-dimensional (3D) models through the construction of mathematical models. Based on these mathematical models, this paper further develop ocean models and measurement models. These models aid in determining the characteristics of different sea models, as well as the properties of measurement signals under various measurement modes and positions. By employing the models constructed, this paper are able to devise optimal measurement paths and modes for specific bodies of water. Subsequently, this paper identify the best measurement methods and their corresponding limitations within those particular waters. Analyzing the optimal measurement techniques and their associated deficiencies in specific waters allows us to draw final conclusions about the measurements taken in those waters. The multibeam line model finds significant applications in numerous fields, encompassing marine topographic mapping, marine ecological research, marine resource exploration, marine environmental monitoring, and marine engineering and harbor construction. In these application areas, multibeam line measurements provide precise and detailed data support, offering critical tools for the effective understanding and management of our marine environments.